Dietary myo-inositol deficiency decreased intestinal immune function related to NF-κB and TOR signaling in the intestine of young grass carp (Ctenopharyngodon idella). Issue 76 (May 2018) - Li, Shuang-An; Jiang, Wei-Dan; Feng, Lin; Liu, Yang; Wu, Pei; Jiang, Jun; Kuang, Sheng-Yao; Tang, Ling; Tang, Wu-Neng; Zhang, Yong-An; Yang, Juan; Tang, Xu; et al.
Abstract: In this study, we investigated the effects of dietary myo -inositol on the intestinal immune barrier function and related signaling pathway in young grass carp ( Ctenopharyngodon idella ). A total of 540 young grass carp (221.33 ± 0.84 g) were fed six diets containing graded levels of myo -inositol (27.0, 137.9, 286.8, 438.6, 587.7 and 737.3 mg/kg) for 10 weeks. After the growth trial, fish were challenged with Aeromonas hydrophila . The results indicated that compared with the optimal dietary myo -inositol level, myo -inositol deficiency (27.0 mg/kg diet): (1) decreased lysozyme (LZ) and acid phosphatase (ACP) activities, as well as complement 3 (C3), C4 and immunoglobulin M (IgM) contents in the proximal intestine (PI), middle intestine (MI) and distal intestine (DI) of young grass carp ( P  < 0.05). (2) down-regulated the mRNA levels of anti-microbial substance: liver expressed antimicrobial peptide (LEAP) 2A, LEAP-2B, hepcidin, β-defensin-1 and mucin2 in the PI, MI and DI of young grass carp ( P  < 0.05). (3) up-regulated pro-inflammatory cytokines [IL-1β (not in DI), TNF-α and IL-8], nuclear factor kappa B P65 (not NF-κB P52), c-Rel, IκB kinaseα (IKKα), IKKβ and IKKγ mRNA levels in the PI, MI and DI of young grass carp ( P  < 0.05); and down-regulated pro-inflammatory cytokines IL-15 (not in DI) and inhibitor of κBα (IκBα) mRNA levels ( P  < 0.05). (4) down-regulated the mRNA levels of anti-inflammatory cytokines [IL-10 (not in DI), IL-11, IL-4/13B (not IL-4/13A), TGF-β1 and TGF-β2], target of rapamycin (TOR), eIF4E-binding proteins 1 (4E-BP1) and ribosomal protein S6 kinase 1 (S6k1) in the PI, MI and DI of young grass carp ( P  < 0.05). All data indicated that myo -inositol deficiency could decrease fish intestine immunity and cause inflammation under infection of A. hydrophila . Finally, the optimal dietary myo -inositol levels for the ACP and LZ activities in the DI were estimated to be 415.1 and 296.9 mg/kg diet, respectively. Highlights: Compared with optimal myo -inositol supplementation: ● Myo -inositol deficiency decreased intestinal antibacterial ability in fish. ● Myo -inositol deficiency aggravated inflammation degree in the intestine of fish. ● Myo -inositol regulated NF-κB and TOR signaling.